Evaluation in PR through current methods and performance indicators. Future trends - Gurgu, Elena; Cociuban, Aristide (Journal of Economic Development, Environment and People, 2017)
Abstract: In today's economic environment, deeply marked by a crisis whose impact continues to spread, there is talk of efficiency. Society efficiency as well as efficiency at company and individual level. Efficiency in the field of public relations professionals is done by evaluating the work done. Although the evaluation is not a new chapter of the communication plan, generated by the economic crisis, but a compulsory one, irrespective of the external environment, we are seeing an increased pressure in this regard. The "client" - the one who runs a campaign - now wishes, more than ever, to know what impact the money has been on. Although the PR world is a complex one, which is generally based on purely creative concepts, in the evaluation the "client" wishes to simplify to the fullest extent of all syllogisms and, finally, a clear answer to one question: what impact did the sum have invested in communication activities?